(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2021)
The essay deals with the case of Catholic associations which bury aborted fetuses when the parents do not give directives in this sense. The analysis focuses particularly on the role of municipalities that grant areas in cemeteries to Catholic associations. The essay supports the thesis that the relationship between municipalities and Catholic associations must respect the principle of secularism and the principle of equality.